Asteroseismology of the double-radial mode δ Scuti star BP Pegasi. Issue 3 (10th March 2022) - Daszyńska-Daszkiewicz, J; Walczak, P; Pamyatnykh, A A; Szewczuk, W
ABSTRACT: Using the All-Sky Automated Survey data, we determine the pulsational frequencies of the high-amplitude δ Scuti star BP Pegasi. The analysis revealed only the two known, independent frequencies that we use to perform the seismic analysis of the star. On the basis of multicolour Strömgren photometry, we independently find that both frequencies can only be associated with radial modes which, according to the frequency ratio, are fundamental and first overtone modes. The models fitting the two frequencies depend strongly on the opacity data. For low values of the mixing-length parameter αMLT ≈ 0.5, only the OPAL seismic models in the post-main-sequence phase of evolution are caught within the observed error box. Seismic models computed with the OP and OPLIB data are much less luminous and cooler. They can only reach the error box if we increase the convection efficiency to at least αMLT = 2.0. Then, including the non-adiabatic parameter f into our seismic modelling, we constrain the value of αMLT . Computing an extensive grid of seismic OPAL models and employing Monte Carlo-based Bayesian analysis, we obtain constraints on various parameters. In particular, the efficiency of envelope convection can be parametrized by αMLT ∈ (0.5,  1.0), depending on the atmospheric microturbulent velocity that amounts to ξ t = 4 or 8 km s −1 .